(untitled) (Journal of Engineering, 2015)
This paper represents an experimentalattempt to predict the influence of CO2-MAG welding variables on the shape factors of the weld joint geometry. Theinput variables were welding arc voltage, wire feeding speed and gas flow rate to investigate their effects on the shape factorsof the weld joint geometry in terms of weld joint dimensions (bead width, reinforcement height, and penetration). Design of experiment with response surface methodology technique was employed to buildmathematical models for shape factors in terms of the input welding variables. Thepredicted models were found quadratic type and statistically checked by ANOVA analysis for adequacy purpose. Also, numerical and graphical optimizations were carried out to determine the optimum values for all responses and input variables. The optimum values of the voltage, wire feeding speed, gas flow rate, WPSF, and WRFF are (20 Volt), (153 cm/min), (10 L/min), (5.222), and (3.970), respectively. And, a good agreement was found between the experimental and predicted results. The weld joint efficiency was found (73%) at the optimum conditions.